Energy‐consistent formulation of the pressure‐free two‐fluid model. (24th January 2023) - Buist, Jurriaan F. H.; Sanderse, Benjamin; Dubinkina, Svetlana; Oosterlee, Cornelis W.; Henkes, Ruud A. W. M.
Abstract: The pressure‐free two‐fluid model (PFTFM) is a recent reformulation of the one‐dimensional two‐fluid model (TFM) for stratified incompressible flow in ducts (including pipes and channels), in which the pressure is eliminated through intricate use of the volume constraint. The disadvantage of the PFTFM was that the volumetric flow rate had to be specified as an input, even though it is an unknown quantity in case of periodic boundary conditions. In this work, we derive an expression for the volumetric flow rate that is based on the demand for energy (and momentum) conservation. This leads to PFTFM solutions that match those of the TFM, justifying the validity and necessity of the derived choice of volumetric flow rate. Furthermore, we extend an energy‐conserving spatial discretization of the TFM, in the form of a finite volume scheme, to the PFTFM. We propose a discretization of the volumetric flow rate that yields discrete momentum and energy conservation. The discretization is extended with an energy‐conserving discretization of the source terms related to gravity acting in the streamwise direction. Our numerical experiments confirm that the discrete energy is conserved for different problem settings, including sloshing in an inclined closed tank, and a traveling wave in a periodic domain. The PFTFM solutions and the volumetric flow rates match the TFM solutions, with reduced computation time, and with exact momentum and energy conservation. Abstract : The pressure‐free two‐fluid model is a model for stratified incompressible flow in ducts, in which the pressure is eliminated through intricate use of the constraints. This article proposes a modification to the model based on the requirement of energy conservation, which makes it consistent with the original pressure‐including two‐fluid model. An energy‐conserving discretization is applied to the improved model, and is extended with an energy‐conserving discretization of the source terms due to gravity acting in the streamwise direction.